2011
DOI: 10.4103/0971-4065.83029
|View full text |Cite
|
Sign up to set email alerts
|

Increased excretion of urinary podocytes in lupus nephritis

Abstract: Podocytes are highly specialized epithelial cells that form part of the filtration barrier in the kidney, and their loss reflects a malfunction in glomerular filtration, which is usually associated with the progression of the disease. Glomerulonephritis is a serious complication that develops in about 50% of the lupus patients and is characterized by proteinuria arising from direct or indirect podocyte injury. To assess the possible role of podocytes in the pathogenesis of lupus nephritis (LN). Urinary and glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Additionally, following the washes some slides were counterstained with 4′,6-diamidino-2-phenylindole (DAPI). Finally, the slides were mounted and examined using fluorescent microscopy [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, following the washes some slides were counterstained with 4′,6-diamidino-2-phenylindole (DAPI). Finally, the slides were mounted and examined using fluorescent microscopy [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, in patients with focal and segmental glomerulosclerosis (FSGS), podocyte loss increases in accordance to the level of injury and might be a marker of disease progression [ 11 , 14 ]. Besides FSGS, urinary podocytes have been detected during the acute phase of other diseases, such as Henoch-Schönlein nephritis [ 10 ], IgA nephropathy [ 10 ], lupus nephritis [ 9 , 15 , 16 ], and also diabetic nephropathy [ 17 ] and preeclampsia [ 18 ]. Moreover, it has been suggested that urinary excretion of podocytes might be helpful to discriminate between acute and chronic stages of glomerular damage [ 19 ].…”
Section: Differentiated Kidney Cells Isolated From Urinementioning
confidence: 99%
“…The WT1 protein has been used as a biomarker of podocyte loss from glomeruli in kidney disease [ 30 , 31 ] and of the presence of damaged podocytes in urinary sediment [ 32 , 33 ]. In this work, we clearly observed a reduction of podocytes in renal biopsies of children with NS and the presence of podocytes in the urine, but the reason for such podocyte detachment is not clear.…”
Section: Discussionmentioning
confidence: 99%